Pengukuran Penerimaan Teknologi Internet Of Things (IOT) Pada Industri Pipa Baja Dengan Metode Tam (Studi Kasus : Perusahaan XYZ) - Afiana Yusita; Dwi Fatrianto Suyatno (CV. SINAR HOWUHOWU, 2026)
XYZ Company has implemented Internet of Things (IoT) technology to support production and monitoring activities. However, concerns regarding the accuracy of system-generated data remain. This study aims to analyze IoT Technology Acceptance using the Technology Acceptance Model (TAM) extended with Trust and Perceived Enjoyment variables. A Mixed Methods approach was employed involving 35 IoT system users. The results indicate that all relationships in the model were significant except the effects of Trust on Perceived Usefulness and Perceived Ease of Use. Qualitative findings reinforced the quantitative results, showing that IoT Technology Acceptance was primarily influenced by Perceived Usefulness, Perceived Ease of Use, and Perceived Enjoyment. Therefore, the extended TAM effectively explains IoT Technology Acceptance at XYZ Company.